Assessing The Mediating Role of Employee Performance in Transforming Social Intelligence, Self-Leadership, and Employee Ability into Organizational Commitment at PT KAI Divre I North Sumatra - Radiman, Radiman; Fitri Wahyuni, Sri; Viola Marpaung, Theresia (AIBPM Publisher, 2025)
At PT KAI Divre I North Sumatra, this study investigates the impact of social intelligence, self-leadership, and employee ability on organizational commitment, with a particular emphasis on the mediating role of employee performance. Employing a rigorous quantitative research design, data were collected via structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among the constructs. The findings reveal that self-leadership significantly enhances employee performance; however, it does not exert a direct effect on organizational commitment. Conversely, social intelligence exhibits a robust positive impact on organizational commitment, despite having no significant effect on employee performance. Additionally, employee ability is positively correlated with employee performance, yet it does not directly influence organizational commitment. Importantly, the anticipated mediating role of employee performance was not supported, suggesting that enhancements in performance alone may be insufficient to strengthen organizational commitment. These results underscore the need for a comprehensive approach in leadership and human resource development that simultaneously fosters performance improvement and cultivates organizational commitment.